Effects of community action on animal vaccination uptake, antimicrobial usage, and farmers’ wellbeing in Ghana: study protocol for a cluster-randomized controlled trial - Francis Sena Nuvey; Günther Fink; Jan Hattendorf; Daniel T. Haydon; Gilbert Fokou; Kennedy Kwasi Addo; Jakob Zinsstag; Clemence Esse-Dibby; Bassirou Bonfoh (One Health)
Infectious animal diseases represent a major constraint to livestock productivity, food security and wellbeing in many developing countries. To mitigate these impacts, farmers frequently use antimicrobials without professional advice, potentially yielding drug residues in livestock products and the food chain, as well as resistant antimicrobial genes. Recent studies identified Contagious Bovine Pleuropneumonia (CBPP) and Peste des Petits Ruminants (PPR) as the diseases most negatively affecting ruminant livestock productivity and farmers’ wellbeing in Ghana. Despite the approval and availability of effective CBPP and PPR vaccines in Ghana, acceptability, affordability, accessibility, and availability of vaccination limit their uptake, with only 15% of farmers regularly vaccinating their herds. During formative qualitative research to identify barriers and potential intervention options, farmers suggested that establishing localized farmer intervention platforms could improve vaccine access. The main idea is the platforms enabling information exchange on livestock vaccines, enhancing service scheduling, and sharing vaccination costs among farmers living in the same locality. We now wish to test formally this hypothesis.Through a cluster-randomized controlled trial, we aim to determine the effect of localized farmer platforms on animal vaccination uptake (primary outcome), antimicrobials use in livestock production, disease-induced mortality in livestock, and livestock farmers’ wellbeing (secondary outcomes). The intervention will be randomized at the community level. The study will involve 460 farming households across 46 rural communities (study clusters). Clusters will be randomized with equal probability to treatment and control (23 communities each). Approximately 10 households per community will be sampled for data collection at baseline, and at 6 and 12 months post-intervention, following prevailing vaccination schedules. We will conduct an intention-to-treat analysis using the available case population. The findings will inform strategies to tackle the impact of infectious livestock diseases on food security, public health and farmers’ wellbeing.Trial registry: https://pactr.samrc.ac.za/; ID No.: PACTR202405854213937.